THE INFLUENCE OF DIGITAL LITERACY ON STUDENT LEARNING - Ervianti Ervianti; Rigel Sampelolo; Muh. Putra Pratama (Fakultas Keguruan dan Ilmu Pendidikan, 2023)
This study aims to determine the influence of digital literacy on the learning outcomes of students of the Educational Technology study program at the Indonesian Christian University of Toraja. Research is a quantitative research type of experiment. This research was conducted at the Indonesian Christian University of Toraja Education Technology Study Program. The sample of this study is all Educational Technology students class of 2021 consisting of 49 students. The total number of samples used was 49 students, using non-random sampling techniques. The results of this study used descriptive analysis and inferential analysis using SPSS 22. The results obtained in this study that in the use of digital literacy of students in producing learning is very releva. From the results of this research, it can be stated that it is significant for student learning outcomes.